Beyond the Visible: Reimagining Legal Evidence Through Causal Realism - Michael Minutillo (Washington University Undergraduate Law Review, 2026)
This paper examines how courts approach legal evidence through the lens of causation and argues for the adoption of Anjan Chakravartty’s framework of causal realism. While legal standards such as Daubert v. Merrell Dow prioritize observable regularities and statistical correlations, they often undervalue explanatory mechanisms rooted in real but unobservable causal processes. Drawing on case studies involving asbestos, climate change, glyphosate, and the opioid crisis, the paper shows how causal realism could better capture the dispositional properties and continuous causal processes central to modern science. Ultimately, the paper advances ideas that surround integrating causal realism into evidentiary standards and how it would potentially allow courts to more fairly and eﬀectively assess complex scientific testimony, especially in cases where waiting for direct observability may undermine justice.
Keywords: legal evidence; causal realism